Internal Audit and Accounting Information System Integration for Construction Project Financial Risk Control: A Qualitative Case Study - Nurlillah Dwinda Wicaksono; Driana Leniwati (Journal of Economic Education and Entrepreneurship Studies, 2026)
This study examines how the integration of Internal Audit and Accounting Information System (AIS) is perceived by organizational actors to support financial risk control in construction projects, using PT MM as an illustrative case. The study was motivated by observations that internal audit at PT MM has traditionally concentrated on the final project stage, while AIS has not been fully utilized as a real-time monitoring and risk-control tool, which informants associated with delayed identification of financial irregularities and heightened exposure to cost overruns, project delays, and cash flow disruptions. This qualitative case study, informed by an interpretive perspective, collected data from seven informants (two internal auditors, two project leaders, two finance staff, and one risk manager) selected through purposive sampling, via an open-ended written questionnaire, non-participant observation, and document review, analyzed using Braun and Clarke's thematic analysis. The findings suggest that, from informants' perspective, Internal Audit and AIS integration is associated with more active project monitoring, earlier attention to financial risks, faster corrective recommendations, and greater perceived transparency and accountability in project financial management, although several implementation challenges emerged, including delayed data updates, inconsistent data entry, inconsistent interdepartmental coordination, and incomplete continuous auditing. The study concludes that, within this single case, Internal Audit and AIS integration appears to strengthen the conditions for financial risk control when supported by integrated information systems, effective cross-functional collaboration, and sustained use of financial information; further research should test whether these perceived mechanisms yield measurable reductions in project financial risk.